2020
DOI: 10.1177/2047487320927610
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and outcomes in ischaemic versus non-ischaemic heart failure across the spectrum of ejection fraction

Abstract: Aims Obesity is related to better prognosis in heart failure with either reduced (HFrEF; left ventricular ejection fraction (LVEF) <40%) or preserved LVEF (HFpEF; LVEF ≥50%). Whether the obesity paradox exists in patients with heart failure and mid-range LVEF (HFmrEF; LVEF 40–49%) and whether it is independent of heart failure aetiology is unknown. Therefore, we aimed to test the prognostic value of body mass index (BMI) in ischaemic and non-ischaemic heart failure patients across the whole spectrum of LVEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 38 publications
4
43
0
1
Order By: Relevance
“…Numerous studies have found generally lower risk in overweight and obese patients with HF, as compared to patients with normal body weight [5,10] and nicely summarised in a recent meta-analysis [12], unless obesity is extreme [13]. Some exceptions have been described based on HF aetiology (ischaemic vs. non-ischaemic) [14,15] or the presence of diabetes [16]. Physiology in HF may change, and factors that increase the risk of HF such as obesity might become unimportant or even protective.…”
Section: The "Obesity Paradox" In Perspectivementioning
confidence: 99%
“…Numerous studies have found generally lower risk in overweight and obese patients with HF, as compared to patients with normal body weight [5,10] and nicely summarised in a recent meta-analysis [12], unless obesity is extreme [13]. Some exceptions have been described based on HF aetiology (ischaemic vs. non-ischaemic) [14,15] or the presence of diabetes [16]. Physiology in HF may change, and factors that increase the risk of HF such as obesity might become unimportant or even protective.…”
Section: The "Obesity Paradox" In Perspectivementioning
confidence: 99%
“…У пациентов с СН в 30-40% случаев диагностируется избыточный вес и до 49% случаев выявляется ожирение, при этом данный "метаболический" клинический фенотип преобладает среди больных СНсФВ [8]. В то же время диапазон встречаемости ожирения в подгруппе пациентов с СНпФВ различной этиологии по данным некоторых обсервационных наблюдательных и оригинальных исследований довольно широк и составляет от 25 до 57% [9][10][11].…”
unclassified
“…In this issue of EJPC, Gentile et al explored the prognostic value of BMI in patients with HF. 13 A total of 5155 patients with either ischaemic or nonischaemic HF were followed up for the end point of 5-year all-cause mortality. The vast majority of patients had heart failure with reduced ejection fraction (HFrEF; left ventricular ejection fraction (LVEF) <40%; 63%), while the rest were equally distributed between heart failure with mid-range EF (HFmEF, LVEF 40-49%; 18%) and heart failure with preserved ejection fraction (HFpEF, LVEF 50%; 19%).…”
mentioning
confidence: 99%
“…Gentile and colleagues 13 should be congratulated for performing a large study with a comprehensive and robust statistical approach. The authors evaluated the independent association of different BMI categories with mortality, after adjusting for important demographic and clinical factors (i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation